Design and Optimization of the Master Manipulator of Minimally Invasive Surgery Robots - Liu Fen; Song Liqiang; Huang Fang; Han Rui; Sang Hongqiang (Jixie chuandong)
The master manipulator is the only interface for human-robot interaction in robot-assisted minimally invasive surgery, and it is of great importance to improve the flexibility and compactness of the master manipulator. In this study, an eight-degree of freedom （DOF） series master manipulator is designed, which can realize the output of positions, attitude and opening and closing torques. The forward kinematic and inverse kinematic models of the master manipulator are respectively established by using the improved D-H parameter method and the analytical method, and the workspace of the master manipulator is verified by the Monte Carlo method, which meets its design requirement. The Jacobian matrix of the master manipulator is solved, the comprehensive performance index of the master manipulator is defined based on the global performance dexterity index and the workspace utilization ratio, and the key link scale parameters are optimized by the genetic algorithm. The results show that the comprehensive performance index of the master manipulator after optimization is 18.41% higher than that before optimization, and the master manipulator is more compact, has better performance besides meeting the design requirements of the workspace.